Rand McNally new millenium world atlas deluxe (Rand McNally, 1998)
An interactive world atlas that offers a 3-D map base, as well as geographic, historic, and scientific content that can be explored with multiple navigation options, customizable maps, with styles for political, physical, and student maps that can be modified for relief and color, and features that can be turned on or off.